Study of changes in hydrodynamic parameters patterns of viscous fluid flow in a flat diffuser; Известия Томского политехнического университета [Известия ТПУ]. Инжиниринг георесурсов; Т. 333, № 10 - Sarukhanyan A. A. Arestak Aramaisovich (2022, 2022)
Заглавие с титульного листа